Blood pressure–controlling behavior in relation to educational level and economic status among hypertensive women in Ghana. Issue 3 (1st September 2018) - Ghose, Bishwajit; Yaya, Sanni
Abstract : Objective: To explore the association between economic status and educational level with self-management behavior (medication adherence, controlling body weight, reducing salt intake, performing physical exercise, reducing alcohol consumption, abstaining from smoking, increasing fruit and vegetable consumption) among hypertensive women in Ghana. Methods: Cross-sectional data on 598 women were collected from the Ghana Demographic and Health Survey of 2014. The association between economic status and educational level with self-management behavior was measured by logistic regression methods. Results: Mean systolic blood pressure and diastolic blood pressure were 131.4 and 86.58 mm Hg, respectively. With regard to self-management behavior, 81.8% of women reported taking medication to control high blood pressure, 44.4% reported controlling body weight, 22.5% reported reducing salt intake, 48.3% reported performing physical exercise, 74.2% reported reducing alcohol consumption, 74.2% reported abstaining from alcohol and smoking, and 20.2% reported consuming more fruits and vegetables. Women living in the wealthiest households had significantly higher odds of maintaining healthy weight, reducing salt intake, and exercising. Conclusion: The findings imply that socioeconomic factors may play important roles in women's adherence to blood pressure–controlling behavior. It is therefore suggested that policy makers focus on improving women's economic status as a strategy to encourage cardiovascular health–promoting behavior. Significance statement: This is the first study to assess the effect of socioeconomic status on blood pressure–controlling behavior among adult women with hypertension in Ghana. The findings could be of crucial importance to health and social policy makers who are working toward reducing the burden of heart diseases and promoting healthy behavior among adult women in Ghana as well as in neighboring countries.